2021
DOI: 10.21511/imfi.18(1).2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the preference of individual retail investors on green bond in India: An empirical study

Abstract: The biggest challenge facing countries, including India, is creating and managing an LCR (low carbon resilient) economy, which balances the need for high growth rates and is environmentally sustainable. The green bond market provides investors the means to help change the economy into an LCR economy. The study was undertaken to understand the key drivers and the factors influencing the individual retail investor’s decision to invest in green bonds. A survey instrument was designed and administered through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…That will allow the issuer to access more capital. Moreover, the ESG score will increase the demand for green bonds considering the increasing confidence of investors, as shown by Prajapati et al (2021). ESG rating influences the investment decision and can be used as an opportunity to access the financial market.…”
Section: Regression Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…That will allow the issuer to access more capital. Moreover, the ESG score will increase the demand for green bonds considering the increasing confidence of investors, as shown by Prajapati et al (2021). ESG rating influences the investment decision and can be used as an opportunity to access the financial market.…”
Section: Regression Resultsmentioning
confidence: 99%
“…The investor motivation theories reveal that the decision to invest in a green bond is related to social, financial, and institutional factors (Prajapati et al 2021). Also, the sustainable theory presents the maximization of the social value, which considers all stakeholders' needs as a core objective (Tolliver et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prajapati et al, 2021) Filho et al (2022). showed that the achievement of SDGs should be considered not only from the point of view of expenditure, but also from an investment approach.…”
mentioning
confidence: 99%